ОСОБЛИВОСТІ ВИКОРИСТАННЯ ТЕСТОВОГО ОЦІНЮВАННЯ ЯКОСТІ ПІДГОТОВКИ МАЙБУТНІХ ФАХІВЦІВ ПІД ЧАС ЕКСТРЕНОГО ДИСТАНЦІЙНОГО НАВЧАННЯ В ЗАКЛАДАХ ФАХОВОЇ ПЕРЕДВИЩОЇ ОСВІТИ (Innovative professional education, 2022)
The multi-instrumental nature of distance learning technologies allows to ensure the quality of the provision of educational services by teachers of institutions of professional advanced education through the use of available means of teaching innovative technologies. During emergency distance learning, the means of test control are particularly effective, which, provided the test tasks are valid, meet the quality criteria for determining the levels of educational achievements of students and allow obtaining objective, reliable results of testing the success of studies.
Keywords: test evaluation, quality of training of future specialists, distance learning technologies, emergency distance learning, professional pre-higher education